2010
DOI: 10.1002/jbmr.118
|View full text |Cite
|
Sign up to set email alerts
|

Wnt10b deficiency results in age-dependent loss of bone mass and progressive reduction of mesenchymal progenitor cells

Abstract: Wnt10b is a canonical Wnt ligand expressed in developing bone and has been linked to mesenchymal progenitor functions in mice and humans. Because Wnt signaling has been shown to play an important role in progenitor maintenance in a variety of adult tissues, we examined bone deposition and growth rates throughout postnatal development in Wnt10b-null mice. Using bone histomorphometry and micro–computed tomographic (µCT) studies, we demonstrate that trabecular bone deposition is slightly enhanced in Wnt10b-null m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
125
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(140 citation statements)
references
References 47 publications
(58 reference statements)
5
125
0
Order By: Relevance
“…Importantly, the increased bone mass phenotype was observed in both cancellous and cortical bone compartments of either sex, which is in line with the impact of Sost/sclerostin deficiency and its pharmacologic blockade on the skeleton (37)(38)(39)(40)(41)(42). This finding differs from the selective impact that individual WNTs can have on either bone compartment (43)(44)(45). In addition, we found increased osteoblast function coupled with a nonsignificant decrease in osteoclast activity as a result of Lrp4 osteoblast/osteocyte deficiency in line with the phenotype of Sost knockout mice (37,38).…”
Section: Discussionsupporting
confidence: 64%
“…Importantly, the increased bone mass phenotype was observed in both cancellous and cortical bone compartments of either sex, which is in line with the impact of Sost/sclerostin deficiency and its pharmacologic blockade on the skeleton (37)(38)(39)(40)(41)(42). This finding differs from the selective impact that individual WNTs can have on either bone compartment (43)(44)(45). In addition, we found increased osteoblast function coupled with a nonsignificant decrease in osteoclast activity as a result of Lrp4 osteoblast/osteocyte deficiency in line with the phenotype of Sost knockout mice (37,38).…”
Section: Discussionsupporting
confidence: 64%
“…Although Wnt10b and Wnt7b are two of the Wnts most commonly associated with bone biology, and Wnt10b is abundantly expressed based on our ISH survey (Wnt7b was moderately expressed), knocking out either Wnt did not produce a drastic skeletal phenotype: Wnt10b knockout mice exhibited mild age-progressive osteopenia (46) and Wnt7b knockout mice were viable and had reduced ossification (53). Hence, to observe more severe bone defects, multiple Wnts have to be knocked out simultaneously, or the Wnt secretion or posttranslational modification process has to be targeted to affect the availability of Wnt ligands.…”
Section: Discussionmentioning
confidence: 81%
“…For example, although Wnt10b is broadly expressed throughout the bone, Wnt4 expression is noticeably higher around the trabecular endosteum compared with the cortical endosteum, and Wnt7b is more highly expressed in the perichondrium than the trabecular and cortical bone regions. The overall most highly expressed Wnt gene is Wnt10b, which is widely considered one of the most important Wnts in bone biology (41)(42)(43)(44)(45)(46). The overall expression levels of all of the Wnt genes are tabulated in Table S1 and ranked in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Si et al found that tightly regulated CCN1/Cyr61 expression may play an important role in Wnt3A-induced osteoblast differentiation of mesenchymal stem cells (39). Stevens et al indicated that Wnt10b, as the only Wnt ligand linking to mesenchymal progenitor function in both humans and mice, is uniquely required for maintenance of mesenchymal progenitor activity in adult bone (40). Some studies revealed that noncanonical Wnt signaling could also play a role in osteogenic differentiation.…”
Section: Mechanisms Of Osteogenic Differentiationmentioning
confidence: 99%